Analysis of the time evolution of COVID-19 lethality during the first epidemic wave in Italy - Balasco , Nicole; d’Alessandro, Vincenzo; Ferrara, Pietro; Smaldone, Giovanni; Vitagliano, Luigi (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: While the entire world is still experiencing the dramatic emergency due to SARS-CoV-2, Italy has a prominent position since it has been the locus of the first major outbreak among Western countries. The aim of this study is the evaluation of temporal connection between SARS-CoV-2 positive tests (cases) and deaths in Italy in the first wave of the epidemic. Methods: A temporal link between cases and deaths was determined by comparing their daily/weekly trends using surveillance data of the period March 2–June 2020. Results: The monitoring of the cases/deaths evolution during the first wave of the outbreak highlights a striking correlation between infections of a certain week and deaths of the following one. We defined a weekly lethality rate that is virtually unchanged over the entire months of April and May until the first week of June (≈13.6%). Due to the rather low number of cases/deaths, this parameter starts to fluctuate in the following three weeks. Conclusions: The analysis indicates that the weekly lethality rate is virtually unchanged over the entire first wave of the epidemic, despite the progressive increase of the testing. As observed for the overall lethality, this parameter uniformly presents rather high values. The definition of a temporal link between cases and deaths will likely represent a useful tool for highlighting analogies and differences between the first and the second wave of the pandemic and for evaluating the effectiveness, even if partial, of the strategies applied during the ongoing outbreak. (www.actabiomedica.it)